Retrofitting model for old building to improve safety factors in building and construction / Nurfaiqah Jamri ... [et al.] - Jamri, Nurfaiqah; Mui, K.W, Horace; Akasah, Zainal Abidin; Nik Soh, Nik Mohd Zaini (2019)
The old building which 30 years or older qualifies as an older building. Some of the following problems may materialize. Continuous maintenance can greatly impact a building's life, as an original quality of construction, but the older building is more likely must find issues impacting and even safety and health. The main purpose of this study is to identify the safety factor of the old flat building environment in building design and construction, to analyse the safety factor model in building design and construction and to evaluate the safety model in building design and construction. In order to carry out this research, a comprehensive literature review was done to identify the safety factor in building and construction. Thus, the information from literature review was used to design a questionnaire for respondents which among them are safety personnel of the company.